UJI BEDA PELANGGARAN TRAFFIC LIGHT BERDASARKAN LOKASI PELANGGARANNYA - Ridayati Ridayati (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2016)
The increasing of the vehicles flow on Yogya-Solo street causing congestion at some points in the Klaten district. The main cause of the congestion is the number of traffic violations which lead to the accidents. Bendogantungan, south Klaten, is one of the most congested point in this district. This study is aimed to determine the causes and the effects of traffic light violations and to examine the difference o f traffic light violations based on the point of violations in the intersection of bendogantungan, Yogya-Solo street. The results show that the practical mind-set of Klaten community in driving has created an instant community. Many people of that community have not realized yet on the importance of traffic regulation, this causes the number of accident. The result of analysis using SPSS 15 shows that there is a significant difference between the one way traffic violation at Empu Sedah street and eastward of Yogya-Solo street. The difference also appears between the one way traffic violations at Empu Sedah street and the westward of Yogya-Solo street. It also happens between the right turn of Ki Ageng Pandanaran street and the westward of Yogya-Solo street.